(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
There have been significant changes in tax frameworks in a few countries in the course of the most recent two decades for an assortment of reasons. The goal of this paper is to dissect the advancement of the tax framework in India since the mid-1990s. The paper depicts and evaluates the presentation of new types of direct and indirect taxes, their revenue and equity suggestions and the triumphs accomplished in their execution. The paper infers that following eight years of change improving the tax framework remains a noteworthy challenge in India.